Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! Let's find the 91st term in the arithmetic sequence 4, 6, 8, ...
In an arithmetic sequence, each term after the first is found by adding a constant difference to the previous term. The general formula to find the nth term of an arithmetic sequence is:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
Where:
- [tex]\( a_n \)[/tex] is the nth term we want to find.
- [tex]\( a_1 \)[/tex] is the first term of the sequence.
- [tex]\( d \)[/tex] is the common difference between the terms.
- [tex]\( n \)[/tex] is the term number.
Given:
- [tex]\( a_1 = 4 \)[/tex]
- [tex]\( d = 6 - 4 = 2 \)[/tex]
We need to find the 91st term ([tex]\( n = 91 \)[/tex]).
Now let's substitute the given values into our formula:
[tex]\[ a_{91} = 4 + (91 - 1) \cdot 2 \][/tex]
First, calculate [tex]\( 91 - 1 \)[/tex]:
[tex]\[ 91 - 1 = 90 \][/tex]
Next, multiply that result by the common difference [tex]\( d \)[/tex]:
[tex]\[ 90 \cdot 2 = 180 \][/tex]
Finally, add this result to the first term [tex]\( a_1 \)[/tex]:
[tex]\[ 4 + 180 = 184 \][/tex]
So, the 91st term of the sequence is:
[tex]\[ a_{91} = 184 \][/tex]
In an arithmetic sequence, each term after the first is found by adding a constant difference to the previous term. The general formula to find the nth term of an arithmetic sequence is:
[tex]\[ a_n = a_1 + (n - 1) \cdot d \][/tex]
Where:
- [tex]\( a_n \)[/tex] is the nth term we want to find.
- [tex]\( a_1 \)[/tex] is the first term of the sequence.
- [tex]\( d \)[/tex] is the common difference between the terms.
- [tex]\( n \)[/tex] is the term number.
Given:
- [tex]\( a_1 = 4 \)[/tex]
- [tex]\( d = 6 - 4 = 2 \)[/tex]
We need to find the 91st term ([tex]\( n = 91 \)[/tex]).
Now let's substitute the given values into our formula:
[tex]\[ a_{91} = 4 + (91 - 1) \cdot 2 \][/tex]
First, calculate [tex]\( 91 - 1 \)[/tex]:
[tex]\[ 91 - 1 = 90 \][/tex]
Next, multiply that result by the common difference [tex]\( d \)[/tex]:
[tex]\[ 90 \cdot 2 = 180 \][/tex]
Finally, add this result to the first term [tex]\( a_1 \)[/tex]:
[tex]\[ 4 + 180 = 184 \][/tex]
So, the 91st term of the sequence is:
[tex]\[ a_{91} = 184 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.